RISK, RESISTANCE AND RESILIENCE OF HIGH-RISK WOMAN ABUSE SURVIVORS - Vukelic, Tamara (My University, 2004)
Once understood as a personal concern, violence against women has been reconceptualized over the past thirty years as a societal problem (Standing Committee on Social Development, 1982). With increasing public attention to woman abuse, researchers have worked to understand what kinds of interventions might ameliorate this tragic phenomenon. Yet very few researchers have asked abused women for their views about interventions designed for their safety by social and police service agencies.
This interview study explored five women's experiences of a Community Safety Protection Program (CSPP), a program intended to prevent future violence or deaths of "high risk" women at the hands of male partners or former partners. The central aim in the research was to situate the CSPP in the context of abused women's struggles and achievements: to examine how the CSPP contributes to their sense of safety, how it enables their resistance, and how it supports their strengths.
The CSPP was found to have benefits beyond the stated intention of the program: it appears that the CSPP may be part of an important shift in the balance of power between a woman and her abusive former partner, changing the nature of her resistance and increasing her entitlement to safety. Interviews also reveal that women's risk of violence persists over time, and suggest careful attention to the match between women's circumstances and the length of time the program is offered. Interviews also highlighted a central paradox: the program's power to protect women can also work to oppress them. The positive impact the CSPP has on women's lives is undeniable; however changes in practice need to take place to mitigate the potential for disempowerment of the recipients of the CSPP.
Keywords: Social Work; Social Work